Creating adaptive athletes: the athletic skills model for enhancing physical literacy as a foundation for expertise - Savelsbergh, G. J. P.; Wormhoudt, R. (Movement & Sport Sciences - Science & Motricité, 2018)
The purpose of the current paper is to advocate that the athletic skills model (ASM) serves as a suitable framework to structure (developmental) movement programs to enhance physical literacy as a foundation for expertise. Taking the non-linear developmental trajectories into account (including the possibility to follow the linear developmental pathway), the ASM applies three "roads" to reach this goal, that is, the concentric approach, creating challenging environments, and exploiting transfer. Each of these separately or in combination with each other will increase the level of physical literacy, that is creating more functional variation leading to an increasement of possibilities for adaptation of those involved (athletes, PE teachers, and coaches). ASM seeks a life-long physical activity participation and to maintain a balance between performance, fitness and health for the recreational as well for the disable and able (elite) athlete.